PSVI-21 Coproantibodies as indicators of the periparturient rise in fecal egg counts in St Croix Sheep. (7th December 2018) - Osei, B; Asiamah, E; Ekwemalor, K; Adjei-Fremah, S; Worku, M
Abstract: The objective of this study was to evaluate IgA and IgE coproantibody levels in fecal samples from periparturient sheep. Coproantibodies are present in the intestinal tract or fecal matter. They are associated with gut infections and are indicators of the local immune response. St Croix sheep are resistant to parasites in part due to their strong immune response. Early indicators of the periparturient and spring rise in parasite levels can aid in management decisions. Fecal samples were collected from 6 adult female St. Croix sheep at -21. -14, -7, +7, +14 and +21 days relative to parturition. Strongyle eggs and coccidia oocytes were counted using the McMaster method. Fecal pellets were homogenized using a Bead Bug homogenizer. The concentrations of IgA and IgE antibodies in the supernatant were evaluated using commercial ELISA for sheep. Data were analyzed using Proc ANOVA in SAS 9.4. The QIAmp kit was used to isolate total microbial DNA, and specific primers were used to amplify Bifidobacteria and Lactobacillus DNA using PCR. A Pearson's correlation analysis was conducted. Both IgA and IgE coproantibodies were detected in feces. IgA coproantibodies increased from 2.7 mg/ml at -21 days to 403.4 mg/ml at +21 days. IgE concentration was highest at day -7 but reduced at day +7 (1601.3 and 1582.9 mg/L respectively). IgA correlated negatively with strongyle eggs (r=0.4). There was no correlation between IgA and coccidia oocytes. IgE correlated positively with strongyle eggs (r=0.7) and negatively with coccidia oocytes (r=0.7). Secretion of IgA and IgE correlated negatively with total microbial DNA, Bifidobacteria (r=-0.2, r=-0.4) and Lactobacillus (r=-0.4, -r=0.2). Detection of coproantibodies may be a useful indicator of the periparturient rise in fecal egg counts, gut health and humoral immunity for management of parasites in small ruminants and should be further evaluated.